2021
DOI: 10.1021/acs.est.0c08565
|View full text |Cite
|
Sign up to set email alerts
|

How Much of the Total Organic Halogen and Developmental Toxicity of Chlorinated Drinking Water Might Be Attributed to Aromatic Halogenated DBPs?

Abstract: Although >700 disinfection byproducts (DBPs) have been identified, >50% of the total organic halogen (TOX) in drinking water chlorination is unknown, and the DBPs responsible for the chlorination-associated health risks remain largely unclear. Recent studies have revealed numerous aromatic halo-DBPs, which generally present substantially higher developmental toxicity than aliphatic halo-DBPs. This raises a fascinating and important question: how much of the TOX and developmental toxicity of chlorinated drinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(72 citation statements)
references
References 85 publications
2
70
0
Order By: Relevance
“…Organic DBPs form when naturally present dissolved organic matter (DOM) reacts with disinfectants such as free available chlorine (i.e., HOCl/OCl – , Cl 2 , and Cl 2 O), , which is effective, inexpensive, and provides residual disinfectant during distribution. , Organic DBPs regulated in the United States (i.e., four trihalomethanes, THMs, and five haloacetic acids, HAAs) represent only a fraction of DBPs that are present in treated water. Known unregulated DBPs, including haloacetonitriles (HANs) or aromatic DBPs, contribute significantly to the toxicity of chlorinated drinking water. Furthermore, the vast majority of organic DBPs produced during chlorination have not yet been identified and their toxicity is unknown. ,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic DBPs form when naturally present dissolved organic matter (DOM) reacts with disinfectants such as free available chlorine (i.e., HOCl/OCl – , Cl 2 , and Cl 2 O), , which is effective, inexpensive, and provides residual disinfectant during distribution. , Organic DBPs regulated in the United States (i.e., four trihalomethanes, THMs, and five haloacetic acids, HAAs) represent only a fraction of DBPs that are present in treated water. Known unregulated DBPs, including haloacetonitriles (HANs) or aromatic DBPs, contribute significantly to the toxicity of chlorinated drinking water. Furthermore, the vast majority of organic DBPs produced during chlorination have not yet been identified and their toxicity is unknown. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…8−12 Furthermore, the vast majority of organic DBPs produced during chlorination have not yet been identified and their toxicity is unknown. 9,10,12,13 DBP formation during disinfection is influenced by both the concentration and composition of DOM, which ranges widely in drinking water sources. Most utilities in the United States rely on surface waters and, as a result, the composition and reactivity of DOM in these sources are well characterized.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[ 30 , 31 , 32 ]. However, recent studies revealed that commonly regulated DBPs cannot be the major contributor to the adverse health effects induced by consuming chlorinated drinking water [ 33 , 34 ]. Compared with regulated DBPs, some emerging DBPs, such as halobenzoquinones, iodinated DBPs, nitrogenous DBPs, and aromatic DBPs, are more worthy of attention [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of human health threats of PHCZs in drinking water requires a thorough understanding of their transformations and fates, especially during potentially prolonged interaction with chlorination disinfectants, such as booster chlorination in delivery systems, which may generate highly toxic secondary chlorinated byproducts. 23 There is growing concern about the artificial chemicals acting as precursors of the DBPs and the possibility of these nextgeneration DBPs exhibiting long-term or even enhanced bioactivity. 24−26 For example, perfluorooctanoate (PFOA) and perfluorooctanesulfonate (PFOS) can be generated from zwitterionic and cationic precursor compounds during chlorination disinfection, and novel chlorination byproducts of tryptophan are formed during water disinfection.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This study mainly focuses on the transformation of PHCZs in drinking water. The assessment of human health threats of PHCZs in drinking water requires a thorough understanding of their transformations and fates, especially during potentially prolonged interaction with chlorination disinfectants, such as booster chlorination in delivery systems, which may generate highly toxic secondary chlorinated byproducts . There is growing concern about the artificial chemicals acting as precursors of the DBPs and the possibility of these next-generation DBPs exhibiting long-term or even enhanced bioactivity. For example, perfluorooctanoate (PFOA) and perfluorooctanesulfonate (PFOS) can be generated from zwitterionic and cationic precursor compounds during chlorination disinfection, and novel chlorination byproducts of tryptophan are formed during water disinfection. , It has been reported that the chlorination process may also lead to the transformation of some organic pollutants to small molecule disinfection byproducts. The transformation processes of PHCZs induced by photolysis have been reported, where dehalogenation, hydroxylation, and hydrolysis are suggested as the major photodegradation mechanisms of PHCZs in liquid solution. However, the transformation of PHCZs during the chlorination process in drinking water has not been investigated, and the generation of possible chlorination byproducts has also not been studied.…”
Section: Introductionmentioning
confidence: 99%